Remediation in Rwanda : Grassroots Legal Forums - Doughty, Kristin Conner (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
Kristin Conner Doughty examines how Rwandans navigated the combination of harmony and punishment in grassroots courts purportedly designed to rebuild the social fabric in the wake of the 1994 genocide.
Frontmatter -- Contents -- Introduction. Harmony Legal Models and the Architecture of Social Repair -- Chapter 1. Silencing the Past: Producing History and the Politics of Memory -- Chapter 2. Escaping Dichotomies: Grassroots Law in Historical and Global Context -- Chapter 3. Gacaca Days and Genocide Citizenship -- Chapter 4. Comite y Abunzi: Politics and Poetics of the Ordinary -- Chapter 5. The Legal Aid Clinic: Mediation as Thick Description -- Chapter 6. Improvising Authority: Lay Judges as Intermediaries -- Conclusion. Legal Architectures of Social Repair -- Notes -- Bibliography -- Index -- Acknowledgments
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed May 30, 2016)
Keywords: Gacaca justice system -- Rwanda; Peace-building -- Rwanda; Postwar reconstruction -- Law and legislation -- Rwanda; Rwandans -- Social conditions